2016
DOI: 10.1120/jacmp.v17i6.6429
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a clinical model for lung cancer patients using stereotactic body radiotherapy (SBRT) within a knowledge‐based algorithm for treatment planning

Abstract: The purpose of this study was to describe the development of a clinical model for lung cancer patients treated with stereotactic body radiotherapy (SBRT) within a knowledge‐based algorithm for treatment planning, and to evaluate the model performance and applicability to different planning techniques, tumor locations, and beam arrangements. 105 SBRT plans for lung cancer patients previously treated at our institution were included in the development of the knowledge‐based model (KBM). The KBM was trained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 20 publications
0
62
0
Order By: Relevance
“…KBP library models are a good way to incorporate the expert knowledge base found from prior patient planning and rapidly utilize this knowledge to predict planning outcomes for new patients. Many groups have utilized in‐house created models applied to a variety of body sites . Most have started with prostate planning due to the simplicity of the site in terms of ease of planning and the bonus of having a database that includes a large number of consistent plans from which to draw.…”
Section: Discussionmentioning
confidence: 99%
“…KBP library models are a good way to incorporate the expert knowledge base found from prior patient planning and rapidly utilize this knowledge to predict planning outcomes for new patients. Many groups have utilized in‐house created models applied to a variety of body sites . Most have started with prostate planning due to the simplicity of the site in terms of ease of planning and the bonus of having a database that includes a large number of consistent plans from which to draw.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have been published for head and neck cancer, 72,79,82 prostate cancer, 62,66,78,83,188 cervical cancer, 78 lung cancer, 75,83,189 spinal metastasis, 63 breast cancer, 65 upper gastrointestinal (GI) cancers, 61,70,76 and lower GI cancers. 190 Foy et al reported that KBP could reduce the VMAT planning of stereotactic body radiotherapy of the spine from 1-1.5 h to around 10-15 min.…”
Section: Clinical Evaluation and Implementation Of Automated Planningmentioning
confidence: 99%
“…Researchers have devoted a considerable amount of efforts in achievement the dose prediction as part of the treatment planning process. The most widely reported approach is the so‐called knowledge‐based planning (KBP) which builds a geometry‐dosimetry correlation prediction model based on prior patient databases of high‐quality treatment plans8‐19 and this approach is currently available in the commercial software, RapidPlan (Varian Medical Systems, Palo Alto, CA) 20. These KBP methods have been shown to improve the plan quality, consistency, and efficiency.…”
Section: Introductionmentioning
confidence: 99%